Antimicrobial Stewardship: A Correct Management to Reduce Sepsis in NICU Settings - Veronica Notarbartolo; Bintu Ayla Badiane; Vincenzo Insinga; Mario Giuffrè (MDPI AG, 2024)
The discovery of antimicrobial drugs has led to a significant increase in survival from infections; however, they are very often prescribed and administered, even when their use is not necessary and appropriate. Newborns are particularly exposed to infections due to the poor effectiveness and the immaturity of their immune systems. For this reason, in Neonatal Intensive Care Units (NICUs), the use of antimicrobial drugs is often decisive and life-saving, and it must be started promptly to ensure its effectiveness in consideration of the possible rapid evolution of the infection towards sepsis. Nevertheless, the misuse of antibiotics in the neonatal period leads not only to an increase in the development and wide spreading of antimicrobial resistance (AMR) but it is also associated with various short-term (e.g., alterations of the microbiota) and long-term (e.g., increased risk of allergic disease and obesity) effects. It appears fundamental to use antibiotics only when strictly necessary; specific decision-making algorithms and electronic calculators can help limit the use of unnecessary antibiotic drugs. The aim of this narrative review is to summarize the right balance between the risks and benefits of antimicrobial therapy in NICUs; for this purpose, specific Antimicrobial Stewardship Programs (ASPs) in neonatal care and the creation of a specific antimicrobial stewardship team are requested.